2022
DOI: 10.3390/jcm12010044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Prostaglandin Analogue Therapy on Central Corneal Thickness: A Systematic Review

Abstract: To investigate whether prostaglandin analogue (PGA) eyedrops have a significant effect on central corneal thickness (CCT), we conducted a systematic search of literature published from 2000 to 2021. Among the studies conducted on topical PGA therapy in open-angle glaucoma or ocular hypertension patients over 18 years old, prospective studies with CCT change as an outcome were included. A single-arm meta-analysis was conducted to assess the overall effect on CCT, and subgroup analysis according to exposure time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The short‐term effects may differ from the long‐term effects. Furthermore, meta‐analyses have shown that topical PGAs significantly decrease central corneal thickness 23,24 . A previous in vitro study showed a decrease in collagen type I levels and corneal thickness in rabbit eyes treated with PGAs and a corresponding decline in corneal thickness in patients treated with PGAs 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The short‐term effects may differ from the long‐term effects. Furthermore, meta‐analyses have shown that topical PGAs significantly decrease central corneal thickness 23,24 . A previous in vitro study showed a decrease in collagen type I levels and corneal thickness in rabbit eyes treated with PGAs and a corresponding decline in corneal thickness in patients treated with PGAs 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation in our study is that a majority of HMG participants were treated with prostaglandin analogues (PGAs). Notably, prior studies have suggested a potential impact of PGAs on anterior segment structures in glaucoma patients [ 37 , 38 ]. However, future longitudinal studies with larger samples are needed to prove these effects and to determine the requisite time for manifestation in myopic patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on changes in corneal thickness (which is part of the fibrous capsule of the eye) during prostaglandin treatment. 14,15 This fact suggests a close relationship between the thickness of the supporting membrane of the eye andthe level of IOP. In our opinion, thinning of the anterior segment of the sclera can be achieved surgically (rounded supraciliary non-penetrating sclerectomies -imitation of anteriorscleral staphyloma in advanced myopia and glaucoma.…”
Section: What Do We Offer?mentioning
confidence: 97%